Maternal Height and Risk of Preeclampsia among Race/Ethnic Groups - Marić, Ivana; Mayo, Jonathan A.; Druzin, Maurice L.; Wong, Ronald J.; Winn, Virginia D.; Stevenson, David K.; Shaw, Gary M. (American Journal of Perinatology, 2019)
Objective Shorter maternal height has been associated with preeclampsia risk in several populations. It has been less evident whether an independent contribution to the risk exists from maternal height consistently across different races/ethnicities. We investigated associations between maternal height and risk of preeclampsia for different races/ethnicities.Study Design California singleton live births from 2007 to 2011 were analyzed. Logistic regression was used to estimate adjusted odds ratios for the association between height and preeclampsia after stratification by race/ethnicity. To determine the contribution of height that is as independent of body composition as possible, we performed one analysis adjusted for body mass index (BMI) and the other for weight. Additional analyses were performed stratified by parity, and the presence of preexisting/gestational diabetes and autoimmune conditions.Results Among 2,138,012 deliveries, 3.1% preeclampsia/eclampsia cases were observed. The analysis, adjusted for prepregnancy weight, revealed an inverse relation between maternal height and risk of mild and severe preeclampsia/eclampsia. When the analysis was adjusted for BMI, an inverse relation between maternal height was observed for severe preeclampsia/eclampsia. These associations were observed for each race/ethnicity.Conclusion Using a large and diverse cohort, we demonstrated that shorter height, irrespective of prepregnancy weight or BMI, is associated with an increased risk of severe preeclampsia/eclampsia across different races/ethnicities.
Keywords: maternal height; preeclampsia; eclampsia; race/ethnicity; BMI; parity